Penerapan Ice Breaking Sebagai Stimulus Minat Belajar Peserta Didik di SDN 04 Kubang Putiah - Rahmadani, Siska; Dewi, Puti Andam; Putri, Yani Mukminah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research refers to students' lack of interest in learning in the learning process. Where the learning carried out tends to use old methods. This is also due to the lack of creativity and interesting innovation in learning, so that students easily feel bored when studying and this has an impact on students' interest and enthusiasm for learning in receiving learning materials. One solution that can be applied to stimulate students' interest in learning again is by thawing the atmosphere during learning, such as implementing the ice breaker "clap one, two, and so on" which is one way to create a fun, interesting, innovative, teaching and learning process. creative and active. The aim of this research is to grow and stimulate students' interest in learning at SDN 04 Kubang Putiah. Data collection was carried out through interviews, observation and documentation. Based on research results from the application of Ice breaking while studying. First, the advantage of implementing Ice Breaking is that it helps eliminate boredom and sleepiness during learning. Second, ice breaking can be done on all subjects, both general and religious, and anyone can do it without special skills. Third, ice breaking can increase and stimulate students' interest in learning to become enthusiastic and passionate about learning again.